Respons Pertumbuhan Bibit Stek Mucuna (Mucuna Bracteata D.C) Pada Media Tanam Limbah Kelapa Sawit Dan Mikoriza - M. Dian Munawan; Chairani Hanum; Mbue Kata Bangun (Jurnal Agroekoteknologi, 2015)
The objecctive of these research was to study response of Mucuna seedling on planting media from waste oil palm and mycorrhiza. This research conducted at the Silau Dunia, PTPN III, District Dolok Masihul, Serdang Bedagai, North Sumatra, on October 2014 to January 2015. The design used randomized block design factorial. The first factor was planting media from palm oil waste with composition: (Top Soil+ Sandy soil; Top Soil+ empty fruit bunches+ Fiber; Top Soil+empty fruit bunches+Solid Decanter; Top Soil+empty fruit bunches+Sludge; Top Soil+ Fiber+ Solid Decanter; Top Soil+ Fiber+ Sludge and Top Soil+ Solid Decanter+ Sludge). The second factor was asosiation with Mycorrhizae (micofer aplication and not). The result showed that planting Media Top Soil+ empty fruit bunches+ Sludge can increased Mucuna growth. Mucuna seedling that symbiosis with mycorrhizae can improve all growth parametrs compared without mycorrhiza aplication.Keywords : Cuttings Mucuna, empty fruit bunches, Fiber, Sludge, Solid Decanter, Mycorrhiza